Hepatic Artery Embolization prior to En Bloc Resection of an Encased Common Hepatic Artery in Adenocarcinoma of the Head of the Pancreas - Aerts, Raymond; Maleux, Geert; Schadde, Erik; Sergeant, Gregory (Case Reports in Medicine, 2013)
A 64-year-old female patient with adenocarcinoma of the head of the pancreas with encasement of the common hepatic artery and portal vein stenosis was reexplored after six cycles of gemcitabine (1000 mg/m2). Prior to surgery, the patient underwent balloon dilation and stenting of the portal vein in addition to successful coil embolisation of the common hepatic artery, proper hepatic artery, and proximal gastroduodenal artery. After embolisation, a pylorus-preserving pancreaticoduodenectomy was performed with resection of the common hepatic artery and portal vein confluens. Pathological examination showed a moderately differentiated pT3N0 (Stage IIa, TNM 7th edition) tumor with negative section margins. We show with this case that in selected cases of periampullary cancer with encasement of the common hepatic artery, it is technically feasible to perform pancreaticoduodenectomy with hepatic artery resection and negative surgical margins. Nevertheless, the oncological benefit of extended arterial resections remains controversial.